Multi-disciplinary management of a patient with a post-traumatised incisor presenting concurrent replacement and inflammatory resorption: a case report - Doğramacı Esma J.; Rossi-Fedele Giampiero; Jones Allan G. (Sciendo, 2015)
This case report describes the multidisciplinary management of a young male who presented with a Class I incisor relationship and bi-maxillary dento-alveolar protrusion on a Class I skeletal base. The occlusion was complicated by an ankylosed and moderately infra-positioned upper left permanent central incisor, an anterior crossbite, crowding, a reduced overbite and centreline discrepancy. The incisor was traumatised and avulsed when the root was immature and the tooth was reimplanted with delay. On referral for orthodontic treatment at age 11.5 years, the upper left central incisor was experiencing ankylosis-related (osseous replacement) resorption and external root resorption simultaneously. Aside from the orthodontic aims, it was important to address the disrupted alveolar development to facilitate later prosthodontic replacement of the upper left permanent central incisor by idealising the inter-coronal and inter-radicular spaces. Treatment consisted of fixed orthodontic appliances in conjunction with the extraction of all second premolars and the upper left permanent central incisor with episodic surgical curettage. An upper Hawlix retainer was provided immediately at debond and a cantilevered resin-retained bridge was placed four months later.